Daucus carrota L. - seed germination and natural infection by Fusarium spp. affected by Pseudomonas spp. - Jošić, Dragana Lj; Cvikić, Dejan; Zdravković, Jasmina; Kuzmanović, Đorđe; Zdravković, Milan; Knežević, Magdalena; Pavlović, Snežana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
The inhibitory effect of indigenous Pseudomonas strains on Fusarium spp. isolated from seeds of a new variety of carrot - ‘Vizija’ and their effects on seed germination were observed. Pseudomonas spp. strains were applied as bacterial suspensions (culture, 106 CFU mL-1) and cell-free supernatant (CFSa -106 and CFSb -108 CFU mL-1) fractions by sowing seeds during 7 (I) and 14 (II) days of incubation. The germination of control ‘Vizija’ seeds was 19% after the first and 40% after the second incubation period. Pseudomonas chlororaphis Q16 strain exhibited statistically significant increases in seed germination with all applied fractions and incubation periods, showing values of 43-62% and 55.5-91%, i.e. increments of 24-43% and 15.5-51% compared to the control, after 7 and 14 days of incubation, respectively. P. chlororaphis K35 showed lower but significantly different seed germination values (38-67%) for all variants, except for 7 days old culture. Pseudomonas sp. Ek1 had weaker seed germination potential, showing statistically significant increment only for CFSa,b (I) and CFSb (II) fractions. All tested Pseudomonas strains inhibited the growth of three Fusarium species isolated from ‘Vizija’ seeds: F. solani, F. oxysporum and F. subglutinans. Natural infection was observed in 20% (I) and 54% (II) of ‘Vizija’ seeds. P. chlororaphis K35 was the most efficient antifungal strain, reducing seed infection 97.5-100%, followed by Q16 with 95-100%, showing no statistically significant mutual difference. Pseudomonas sp. Ek1 showed a weaker antifungal activity and reduced seed infection by 85-96.75%. The application of P. chlororaphis Q16 and K35 as strains effective in improvement of carrot seed germination and growth inhibition of the seed pathogens F. solani, F. oxysporum and F. subglutinans, can be further tested in carrot production for more beneficial effects.